Diterpenoids from the aerial parts of Euphorbia antiquorum and their efficacy on nitric oxide inhibition. (December 2020) - Choodej, Siwattra; Hanthanong, Sujitra; Aree, Thammarat; Pudhom, Khanitha
Abstract: Eight previously undescribed diterpenoids of different types were isolated from ethyl acetate extract of the aerial parts of Euphorbia antiquorum L., along with fifteen known diterpenoids. Their structures and configurations were determined by 1D and 2D NMR, MS, and electronic circular dichroism (ECD). Additionally, the absolute configuration of ent -12-oxo-2, 3-secobeyer-15-en-2, 3-dioic acid-3-methyl ester was confirmed through single-crystal X-ray diffraction. Efficacy of the compounds on lipopolysaccharide (LPS)-stimulated nitric oxide (NO) production in murine macrophage J774.A1 cells was evaluated. ent -15-Acetoxylabda-8(17), 13 E -diene-3-one, ent -15-oxolabda-8(17), 13 E -diene-3-one and rhizophorin B was significantly suppressed NO production with IC50 values of 11.7, 12.5 and 16.1 μM, respectively. Graphical abstract: Eight undescribed diterpenes (1 –8 ) were isolated from the aerial parts of Euphorbia antiquorum . Two undescribed labdanes (1 –2 ) suppressed NO production significantly with IC50 values of 11.7, 12.5 and 16.1 μM, respectively. Image 1 Highlights: Eight undescribed (1 -8 ) and fifteen related known (9 -23 ) diterpenes were isolated from the aerial parts of E. antiquorum . The anti-inflammatory activity of the isolated diterpenes was evaluated. Two undescribed labdanes (1 and 2) exhibited significantly inhibitory effect on LPS-induced NO production in J774.A1 cells.